UMPSA and NIT Yonago College strengthen ties through successful summer programme - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2024)
KUALA LUMPUR, 29 February 2024 - 29th to March 5th, 2024 - The Summer Programme organised by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) for students from the National Institute of Technology, Yonago College, Japan, concluded successfully on 5th March 2024.